Silica@lipase hybrid biocatalysts with superior activity by mimetic biomineralization in oil/water two-phase system for hydrolysis of soybean oil. (15th April 2022) - Kuang, Geling; Du, Yingjie; Lu, Shihai; Wang, Zichen; Zhang, Zhijin; Fan, Xianwei; Bilal, Muhammad; Cui, Jiandong; Jia, Shiru
Abstract: Enzymatic hydrolysis of vegetable oils is crucial for its potential application in foods and drugs. However, the poor activity of free lipase hinders the reaction. Herein, inspired by lipase interface activation, a novel silica@lipase hybrid biocatalyst with a superior catalytic activity for hydrolysis of vegetable oils was developed though the sol-gel biosilicification approach in the oleic acid/water two-phase system. The resultant silica@lipase hybrid biocatalyst exhibited 13.5-fold higher activity than free lipase, and excellent storage stability. After 100 days of storage, the free lipase absolutely loss hydrolytic activity whereas the silica@lipase hybrid biocatalyst still retained 197.4% of its initial activity. In particular, hydrolysis yield of soybean oil by the hybrid biocatalyst reached 98.8% within only 4 h, which is the fastest value recorded in the current literature. After 5 consecutive cycles, hydrolysis yield still retained up to 63%. Therefore, this strategy provides a facile and efficient method for preparing lipase hybrid biocatalysts with high hydrolysis activity. Graphical abstract: Image 1 Highlights: - A novel silica@lipase hybrid biocatalyst for hydrolysis of vegetable oils was prepared. - Silica@lipase hybrid biocatalyst exhibited superior hydrolysis activity and excellent storage stability. - A 98.8% hydrolysis yield of soybean oil was reached within only 4 h.